-10t=90

Simple and best practice solution for -10t=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10t=90 equation:


Simplifying
-10t = 90

Solving
-10t = 90

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Divide each side by '-10'.
t = -9

Simplifying
t = -9

See similar equations:

| 0.4/24 | | [7-2y]-8=-3 | | 2x^2-22x-12=0 | | -2[d+6]=-10 | | (-15)(-17)= | | x/5=x/3-2 | | -8x+2+5x=-13 | | 6x-(3x-8)=29 | | -6+-8g=-62 | | b^3+b^2+1=0 | | 5=d+6 | | -80=8(b-5)-10(b+6) | | 10k^2-24=-12k | | -18-4a=-2 | | 20x+5x+1=101 | | x-9/10=21/10 | | (2y-5)/(6x-7y)=x | | 42-53+(-34)-56= | | Cos(3.14+6)=0 | | w/6*30 | | 42x-5=-20 | | 3x-(2-x)=x-2(x+3) | | -7-7(1-8x)=-126 | | 4x-2=7+(4x-9) | | 3/4x-6=0 | | -1-6(1+3n)=1 | | 0.7+0.3= | | K+5=k+9 | | 6ab+3b^2-8ab+5b^2-10=0 | | 4[y+1]=-8 | | 7x+8x-10= | | (65)q+13=(2)q+(0) |

Equations solver categories